2001
DOI: 10.1177/1524838001002002001
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder (PTSD) in Victims of Domestic Violence

Abstract: The objectives of this research were to analyze data from literature based on studies of battered women to determine (a) the correlation of domestic violence and post-traumatic stress disorder (PTSD), (b) the best treatment strategies for PTSD, and (c) the evidence of PTSD treatment effectiveness with battered women. Findings were (a) symptoms of battered women are consistent with PTSD symptoms; (b) certain populations are at higher risk of developing PTSD symptoms; (c) intensity, duration, and perception of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
199
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(214 citation statements)
references
References 57 publications
6
199
3
4
Order By: Relevance
“…They include injury, chronic pain, gastrointestinal and gynecological problems including sexually transmitted diseases, as well as depression, anxiety, posttraumatic stress disorder (PTSD), low self-esteem, sleep and appetite disturbances, suicidal ideation, and somatization (D. Campbell, 1999;Campbell, Sharps, Gary, Campbell, & Lopez, 2002;J.C. Campbell, 2002;Gerlock, 1999;Holmes & Resnick, 1998;Jones, Hughes, & Unterstaller, 2001;Kaslow et al, 2000;Kaslow et al, 1998;Krishnan & Hilbert, 2001). …”
mentioning
confidence: 99%
“…They include injury, chronic pain, gastrointestinal and gynecological problems including sexually transmitted diseases, as well as depression, anxiety, posttraumatic stress disorder (PTSD), low self-esteem, sleep and appetite disturbances, suicidal ideation, and somatization (D. Campbell, 1999;Campbell, Sharps, Gary, Campbell, & Lopez, 2002;J.C. Campbell, 2002;Gerlock, 1999;Holmes & Resnick, 1998;Jones, Hughes, & Unterstaller, 2001;Kaslow et al, 2000;Kaslow et al, 1998;Krishnan & Hilbert, 2001). …”
mentioning
confidence: 99%
“…Additionally, psychotherapeutic treatments for victims of trauma, for example, those with Post Traumatic Stress Disorder (PTSD), have, until more recently, tended to focus on victims of conflict or rape and not women who have experienced domestic violence [37]. Although Hughes and Jones [38] note that research in the US has shown that women victims of domestic violence often meet PTSD criteria, standardized PTSD assessment by trained professionals is needed as well as 'greater public health involvement for prevention, identification, and medical treatment of domestic violence and PTSD' ( [38], p. 5).…”
Section: The Impact Of Domestic Violence On Women's Mental Healthmentioning
confidence: 99%
“…The deleterious effects of intimate partner abuse go beyond physical wounds and encompass a wide range of negative psychological consequences. These include depression (Cascardi & O'Leary, 1992;Gelles & Harrop, 1989;Gleason, 1993), low self-esteem (Cascardi & O'Leary, 1992;Sackett & Saunders, 1999;Scott-Giba, Minne, & Mezney, 1995;Trimpey, M., 1989), feelings of self-blame (Cascardi & O'Leary, 1992;Clements & Sawhney, 2000), heightened stress and anxiety (Trimpey, 1989), posttraumatic symptoms and posttraumatic stress disorder (PTSD) (Jones, Hughes, & Unterstaller, 2001), and increased social isolation (Pressman, 1989).…”
Section: Characteristics Of Partner Abusementioning
confidence: 99%